Expert System to Diagnose the Level of Learning Stress in High School Students Using the Forward Chaining Method - Putri Amalia, Cut Rizki (International Journal Education and Computer Studies (IJECS), 2021)
The research objective is to design an expert system to diagnose the stress level of learning in high school students using the web-based Forward Chaining method. It is hoped that it can be used as an initial alternative to determine the level of stress experienced by students in learning. The research method fully uses a system development model consisting of the need for stages, making prototypes, evaluation stages, and system maintenance. The results of this study succeeded in making an expert system design to diagnose the stress level of learning in high school students using the Forward Chaining method and analyzing the results of the IF THEN ELSE calculations using Forward Chaining.